Partially Information Coupled Polar Codes - Xiaowei Wu (IEEE Access, 2018)
We propose a new class of partially information coupled (PIC) polar codes to improve the transmission efficiency of transport block (TB)-based communication standards. In the proposed PIC polar codes, every two consecutive systematic polar code blocks (CBs) in a TB are coupled by sharing a few systematic information bits. Dummy bits are inserted at the two ends of the TB to construct terminated PIC polar codes. We propose a CB decoding scheme which only uses the information associated with correctly decoded coupled bits to mitigate the serious error propagation problem in successive cancellation based polar code decoding algorithms. We also propose an inter-CB decoding scheme which realizes a windowed decoder with variable window size to achieve a flexible tradeoff between the decoding performance and complexity. We derive a closed form expression for the TB error rate (TBER) of the PIC polar codes. We further optimize the coupling scheme based on the derived TBER. Simulation results confirm the effectiveness of the TBER analysis and the coupling scheme optimization results. They also show that the PIC polar codes can significantly outperform the uncoupled polar codes for various code rates with a slightly increased decoding complexity.